Pengaruh Brand Awareness, Brand Image, dan Brand Equity, terhadap Peningkatan Repurchase Intention pada Produk Chatime - Sodikin, Ananda Putri; Misti Hariasih; Febriansah, Rizky Eka (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine and analyze the effect between Brand Awareness, Brand Image, and Brand Equity on increasing Repurchase Intention on Chatime products. This study uses a quantitative approach with a population of all consumers from adolescents to adults who have bought and consumed Chatime products> 1 time in the Sidoarjo and Pasuruan areas, then for the total sample of this study, which amounted to 100 people using non probability sampling techniques. Then for data collection techniques through distributing questionnaires, the data will be processed using data analysis techniques using Multiple Linear Regression Analysis, Data Instrument Test (Reliability Test and Validity Test), Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Hypothesis Test (T Test), and Coefficient of Determination (R2). Data processing in this study used the SPSS application (Version 25). From several tests carried out, the results show that there is a significant influence between Brand Awareness, Brand Image, and Brand Equity on increasing Repurchase Intention on Chatime products. From these results it can be seen that a product can become a product that is favored by the public if the product itself can create a strong memory through a good image and value in the minds of the public.